2006
DOI: 10.1002/cncr.22059
|View full text |Cite
|
Sign up to set email alerts
|

Differences in survival among patients with urachal and nonurachal adenocarcinomas of the bladder

Abstract: Background The National Institute for Occupational Safety and Health (NIOSH) conducted a health hazard evaluation (HHE) of a water‐damaged school in New Orleans (NO), Louisiana. Our aim in this evaluation was to document employee health effects related to exposure to the water‐damaged school, and to determine if VCS testing could serve as a biomarker of effect for occupants who experienced adverse health effects in a water‐damaged building. Methods NIOSH physicians and staff administered a work history and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
172
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(183 citation statements)
references
References 46 publications
3
172
2
6
Order By: Relevance
“…As mentioned earlier, peritoneal spread and local invasiveness are essential and defining for pmp, and surgical management (radical or partial cystectomy with en block resection of tumour, urachal remnant, umbilicus, and posterior rectus abdominus facia) might be insufficient for urachal adenocarcinoma 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, peritoneal spread and local invasiveness are essential and defining for pmp, and surgical management (radical or partial cystectomy with en block resection of tumour, urachal remnant, umbilicus, and posterior rectus abdominus facia) might be insufficient for urachal adenocarcinoma 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The second independent prognostic factor is the histologic grade of the causative malignant lesion 2,7,35,[41][42][43]49 . According to data published by Ronnett and colleagues 7 , the 5-year survival rate in patients with pmp of appendical origin is 84% for patients with dpam, 37.6% for patients whose lesions have intermediate features, and only 6.7% for patients with pmca.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it remains unclear whether the survival of patients with urachal adenocarcinoma varies from that of patients with non-urachal adenocarcinomas. Wright et al (19) identified that urachal cancer possessed a significantly better prognosis than non-urachal cancer, while Mostofi et al (20) hypothesized that urachal adenocarcinomas were associated with a significantly worse prognosis. In addition, Dandekar et al (21) considered there to be no significant differences between the two carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast with the much more frequent transitional cell cancers of the bladder, urachal cancer typically occurs in a younger patient population, with many reports indicating a median age at diagnosis of approximately 47-56 years. [2][3][4] While some investigators report a predominantly male patient population, 5 others suggest a more balanced distribution between male and female patients. 3,4 Unfortunately, there are many patients who present with metastatic disease which currently is not likely to be curable.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] While some investigators report a predominantly male patient population, 5 others suggest a more balanced distribution between male and female patients. 3,4 Unfortunately, there are many patients who present with metastatic disease which currently is not likely to be curable. There is no standard chemotherapy regimen for these patients.…”
Section: Introductionmentioning
confidence: 99%